Are plant–soil feedback responses explained by plant traits?. Issue 2 (3rd July 2014) - Baxendale, Catherine; Orwin, Kate H.; Poly, Franck; Pommier, Thomas; Bardgett, Richard D.
Summary Plant–soil feedbacks can influence plant growth and community structure by modifying soil biota and nutrients. Because most research has been performed at the species level and in monoculture, our ability to predict responses across species and in mixed communities is limited. As plant traits have been linked to both soil properties and plant growth, they may provide a useful approach for an understanding of feedbacks at a generic level. We measured how monocultures and mixtures of grassland plant species with differing traits responded to soil that had been conditioned by model grassland plant communities dominated by either slow‐ or fast‐growing species. Soils conditioned by the fast‐growing community had higher nitrogen availability than those conditioned by the slow‐growing community; these changes influenced future plant growth. Effects were stronger, and plant traits had greater predictive power, in mixtures than in monocultures. In monoculture, all species produced more above‐ground biomass in soil conditioned by the fast‐growing community. In mixtures, slow‐growing species produced more above‐ground biomass, and fast‐growing species produced more below‐ground biomass, in soils conditioned by species with similar traits. The use of a plant trait‐based approach may therefore improve our understanding of differential plant species responses to plant–soil feedbacks, especially in a mixed‐species environment.